Konflik Perebutan Sumber Daya Alam: Studi Kasus: Perebutan Lahan Antar Pemerintah Desa dan Pemilik Lahan di Pantai Uinian - Hasada Sandralina Poto; Ananias R.P Jacob; Frans Wilmat Muskanan (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to identify the causes of the conflict, analyze its impacts on natural resource management, and examine it through Karl Marx’s conflict theory. This research employed a qualitative method with a case study approach. Primary data were obtained through in-depth interviews with landowners, the village government,and community leaders. Secondary data were collected from official documents and related literature. Data analysis was conducted descriptively and qualitatively, referring to Karl Marx’s key concepts such as class conflict, control over the means of production, and alienation. The findings reveal that the conflict is caused by unclear land ownership status, the village government’s economic interests, lack of communication and transparency, and overlapping regulations. The impacts include hampered natural resource management and conservation, uncontrolled exploitation of resources, decreased community participation in sustainable tourism development, and potential environmental damage due to uncoordinated land use. Based on Karl Marx’s analysis, the conflict reflects class struggle between landowners as the dominant class and the village government as the managing class seeking to take over the resources. This study suggests the need for clear regulations, transparent decision-making processes, and active participation from all parties to achieve fair and sustainable natural resource management.